Hemoadsorption in critically ill neonatal and pediatric patients: a retrospective cohort study from a Latin American tertiary center - Piñeres-Olave, Byron Enrique; Herrera-Vargas, Jhojan Sebastian; Tibaduiza, Daniel; Marin-Agudelo, Alejandro; Sarmiento, María Piedad; Salazar, Sandra; Niño-Jaimes, Laura; Arango-Mesa, Natalia (Frontiers in Medicine, 2025)
IntroductionExtracorporeal blood purification therapies, such as hemoadsorption, are increasingly utilized in intensive care to modulate inflammation, improve organ function, and reduce vasoactive support. However, data on their use in neonatal and pediatric populations remain limited, particularly in low-resource settings. This study aimed to evaluate clinical and laboratory outcomes in critically ill pediatric patients receiving hemoadsorption therapy alongside extracorporeal organ support.MethodsWe conducted a single-center retrospective cohort study in a tertiary neonatal and pediatric intensive care unit in Latin America. Eleven critically ill patients received hemoadsorption using CytoSorb® or Oxiris® in combination with continuous renal replacement therapy (CRRT) and/or extracorporeal membrane oxygenation (ECMO). We assessed organ dysfunction scores (PELOD-2), vasoactive-inotropic score (VIS), inflammatory markers (CRP, lactate), oxygenation parameters, and liver and hematologic profiles before and after therapy.ResultsHemoadsorption was associated with reductions in PELOD-2 (median 11–7; p = 0.036) and VIS (median 75–6; p = 0.014). Lactate levels decreased significantly (p < 0.001), and oxygenation improved (PaO₂/FiO₂, median 69–104; p = 0.042). CRP levels declined without reaching statistical significance. Liver and hematologic markers remained largely unchanged. 28-day-mortality was 54.5%.DiscussionHemoadsorption in conjunction with CRRT and/or ECMO showed potential to improve hemodynamic stability, oxygenation, and inflammation in critically ill pediatric patients. These findings support further investigation of hemoadsorption as an adjunctive therapy in pediatric critical care, especially in resource-limited environments.